Level of Preference Surabaya Students in Choosing Instant Noodle Using Linier Regression Method - Murnawan, Hery; Mayangsari, Adhindha Putri; Prihono (UNIPA PRESS, 2024)
The current rapid development of the times demands very high levels of activity, and of course to be able to carry out these various activities requires energy whose main source of energy is food. Currently, many students want to be more practical in consuming food, one of which is instant noodles. This research aims to determine the relationship between taste, ease of purchase and price on the level of preference of Surabaya students for consuming instant noodles. The type of research is linear regression. The population in this study were students from the city of Surabaya and the sample was 38 people. The data collection technique is carried out by filling out a questionnaire. Next, the data was analyzed via linear regression. The results of the research concluded that taste, ease of purchase and price both influence the level of student preference for consuming instant noodles. The factor that has the lowest influence on students' preference for consuming instant noodles is ease of purchase. Students' knowledge of taste and price is relatively good and the availability of instant noodles among students is quite good.